Предмет: Алгебра,
автор: Filka7
Решить уравнение :
2х/х-1 + 3/x+1=3x+1/х^2-1
Ответы
Автор ответа:
0
2x/(x - 1) + 3/(x + 1) =(3x + 1)/(x² - 1)
ОДЗ:
x² - 1 ≠ 0
x ≠ ±1
2x(x + 1)/(x² - 1) + 3(x - 1)/(x² - 1) = (3x + 1)/(x² - 1)
(2x² + 2x + 3x - 3 - 3x - 1)/(x² - 1) = 0
2x² + 2x - 4 = 0
x² + x - 2 = 0
x1 + x2 = -1
x1•x2 = -2
x1 = -2
x2 = 1 - не уд. ОДЗ.
Ответ: х = -2.
ОДЗ:
x² - 1 ≠ 0
x ≠ ±1
2x(x + 1)/(x² - 1) + 3(x - 1)/(x² - 1) = (3x + 1)/(x² - 1)
(2x² + 2x + 3x - 3 - 3x - 1)/(x² - 1) = 0
2x² + 2x - 4 = 0
x² + x - 2 = 0
x1 + x2 = -1
x1•x2 = -2
x1 = -2
x2 = 1 - не уд. ОДЗ.
Ответ: х = -2.
Автор ответа:
0
Похожие вопросы
Предмет: Математика,
автор: borinskaoksana42
Предмет: Алгебра,
автор: teachhuu
Предмет: Русский язык,
автор: 4645c73a8984
Предмет: Математика,
автор: сергей141
Предмет: География,
автор: простапя